3R and 2H polytypes of MoS2: DFT and DFPT calculations of structural, optoelectronic, vibrational and thermodynamic properties. (December 2017) - Coutinho, S.S.; Tavares, M.S.; Barboza, C.A.; Frazão, N.F.; Moreira, E.; Azevedo, David L.
Abstract: We report the results of a theoretical study on the behavior of the structural, optoelectronic, vibrational, including infrared and Raman theoretical spectra, phonon spectrum, and thermodynamic properties of 3R- and 2H- polytypes of molybdenum disulfide (MoS2 ) using density functional theory (DFT) considering both the local density and generalized gradient approximation, LDA and GGA, respectively. Calculated lattice parameters are close to the experimental measurements, and an indirect band gap E(A → K Γ ) = 1.33 eV (0.68 eV) was obtained within the GGA (LDA) level of calculation, considering the 3R-polytype, and for the 2H- polytype an indirect band gap E( Γ → K Γ ) = 1.30 eV (0.70 eV) was obtained within the GGA (LDA) approximation. The complex dielectric function and absorption of 3R-MoS2 and 2H-MoS2 polytypes were shown to be sensitive to the plane of polarization of the incident light. The phonon dispersion relation together with density of states (DOS) as well as theoretical peaks of the infrared (IR) and Raman spectra in the frequency range of 0–800 cm −1 was analyzed and assigned, considering the norm-conserved pseudopotentials. The thermodynamic potentials, the specific heat at constant volume and Debye temperature of the 3R-MoS2 and 2H-MoS2 polytypes are also calculated, whose dependence on the temperature are discussed. Highlights: Properties of polytypes 2H and 3R of MoS2 are presented. Results on Electronic, Vibrational, Optical and Thermodynamical properties. For MoS2 3R polytype, entirely new results are presented. Synthesis of both phase (2H and 3R) occur non-spontaneously.